DIFFERENCES OF MALE AND FEMALE STUDENTS’ UNDERHAND SERVES ABILITY IN MINI VOLLEY BALL BASED ON DEMONSTRATION METHOD - Remon Syah; Rini Anita (State Institute of Islamic Studies Batusangkar, 2021)
This research is aimed at finding whether demonstration method could enhance students’ ability in conducting underhand services at mini volley ball and how it is viewed in gender differences. The research design was a classroom action research by using two cycles at the fourth grade of SDN 20 Bungo Tanjung. The research result shows that there is an improvement on students’ underhand serves ability in applying demonstrastion method for about 23,8%. Cyle 1 is 66,7 % while at cycle 2 is 90,5%. Meanwhile for gender differences, male students are much better than female students in conducting underhand serves. In short, the use of demonstration method can enhance students’ ability in doing underhand serves.